Recognition and naming of the sentence content in deaf children through verbal and non-verbal approach - Salkić, Naim; Švraka, Emira; Pašalić, Arzija (Technium Social Sciences Journal, 2020)
The aim of the research is to determine the effects on the recognition and naming of certain sentence structures through a verbal and non-verbal approach, or through the use of a verbal and non-verbal communication channel. The study was conducted on a sample of 30 deaf pupils at age from 11 to 14 years. As a measurement instrument, a modified image description test was used. The test consisted of six complexes, illustrated sentences, in which the actions and subjects performing certain actions are shown in the picture sequence in a way that deaf children understand. The descriptive analysis method was used for data processing. Measures of central tendencies and variations have been made. Testing the difference between verbal and non-verbal approach was performed by t-test. The correlation between the chronological age and the recognition and naming of the spoken structures were verified through the non-verbal approach. The results of the research have shown that respondents have achieved better results in recognizing and naming spoken content using the non-verbal communication channel, that there is a statistically significant difference in the use of verbal and non-verbal communication approaches in recognizing and naming spoken content, and that there is a high correlation between the chronological age of respondents and recognizing and naming of spoken content through a non-verbal approach.